Anomalous Ising freezing times. (23rd September 2020) - Denholm, J; Hourahine, B
Abstract: We measure the relaxation time of a square lattice Ising ferromagnet that is quenched to zero-temperature from supercritical initial conditions. We reveal an anomalous and seemingly overlooked timescale associated with the relaxation to 'frozen' two-stripe states. While close to a power law of the form ∼ L ν, we argue this timescale actually grows as ∼ L 2 ln L, with L the linear dimension of the system. We uncover the mechanism behind this scaling form by using a synthetic initial condition that replicates the late time ordering of two-stripe states, and subsequently explain it heuristically.